(untitled) (Coordinates of Public Administration, 2026)
The article provides a socio-philosophical and governance-oriented review of contemporary scholarly discourse on societal consolidation and the renewal of public authority. It уточnifies the concept of consolidation as a multidimensional process of integrating social groups around shared values, goals, and norms, manifested in increased social trust, solidarity, mutual responsibility, and support for legitimate institutions. The study identifies the key parameters that shape the dynamics of consolidation in Ukrainian society under the conditions of the russian federation’s armed aggression against Ukraine: value- and identity-related factors (national identity, civic belonging, shared meanings), institutional factors (trust in the state, institutional capacity, quality of public services), communicative factors (the effectiveness of state and societal communication, countering disinformation), socio-economic factors (fairness in resource allocation, support for vulnerable groups), as well as security and territorial factors (community resilience, integration of internally displaced persons, recovery of de-occupied territories). The relevance of the topic is driven by the fact that, in wartime, consolidation functions not only as a socio-psychological necessity but also as a strategic resource for state resilience. External attempts to fragment society along ideological, linguistic, regional, or ethno-cultural lines intensify the need for a form of public authority capable of acting as an integrator of societal interests and a provider of a shared vision for the future. Accordingly, renewed public authority must be able to formulate and implement a value-based unifying framework of the Ukrainian national idea, aimed at strengthening social cohesion, national unity, and solidarity, as well as enhancing trust in institutions and rules. The article emphasizes that renewing public authority cannot be reduced to formal organizational adjustments or personnel rotations. Rather, it entails a structural and cultural transformation of public administration: rethinking governance approaches (from administrative control to service orientation and results-based management), restructuring engagement with the public (from one-way informing to co-creation of decisions and partnerships), strengthening the institutional capacity of the state apparatus, and introducing effective mechanisms of accountability, integrity, and transparency. These processes acquire particular significance in the context of wartime challenges, rapid societal change, globalization pressures, digital transformation of governance, and rising public expectations regarding the fairness, effectiveness, and human-centeredness of state institutions.